PENERAPAN DENGAN KEGIATAN KOMUNIKATIF DI KELAS UNTUK MENINGKATKAN KELANCARAN BERBICARA - Trisanti, Novia (Universitas Negeri Semarang, 2010)
This study has an objective to increase the fluency of English Language and Literaturestudents of Unnes in speaking class by using the materials which can be incorporatedby the stages of critical thinking and communicative activities. The research methodwas classroom action research (CAR). The research was conducted in two cycles.Each cycle consisted of four meetings. In the first cycle, the students appliedcommunicative activity such as group and class discussion. In the cycle 2, the studentshad debate simulation. The research revealed that the use of materials which could beincorporated with critical thinking process could lead the students to think critically incommunicative activities. Those activities improved the students fluency in speakingEnglish, especially students of English Department, Faculty of Languages and Arts,Unnes. The improvement was proven by the improvement of students score betweenpretest with 63 total score and posttest with 72 total score. Furthermore, the studentsattitude dealing with the ability to solve the critical problem, expressing criticalopinion, and of course their speaking fluency in giving critical solution improved.critical thinking, kegiatan komunikatif, kelancaran berbicara